Serum levels of galectin-3 in idiopathic inflammatory myopathies: a potential biomarker of disease activity. (8th August 2020) - Watanabe, Eri; Kato, Kazunori; Gono, Takahisa; Chiba, Emiko; Terai, Chihiro; Kotake, Shigeru
Abstract: Objectives: Galectin-3 is involved in various biological activities, including immune activations and fibrosis. Idiopathic inflammatory myopathies (IIMs) are autoimmune diseases of unknown aetiology, often complicated by interstitial lung disease (ILD). The aim of this study was to evaluate the expression of galectin-3 in sera and tissues of patients with IIM and assess the associations of galectin-3 with patient characteristics and disease activity. Results: Serum galectin-3 levels were significantly higher in IIM patients than in healthy controls. The serum galectin-3 levels positively correlated with serum levels of inflammatory markers and proinflammatory cytokines/chemokines and the Myositis Intention-to-Treat Activity Index. Stratification analysis revealed that patients with IIM-associated ILD (IIM-ILD) had significantly higher levels of serum galectin-3 than those without IIM-ILD. In addition, patients with acute/subacute interstitial pneumonia had significantly higher levels of serum galectin-3 than those with chronic interstitial pneumonia. Furthermore, serum galectin-3 levels in IIM-ILD patients correlated with the radiological assessments of parenchymal lung involvement and treatment response. Immunohistochemical analysis revealed that galectin-3 was expressed in inflammatory cells of myositis and dermatitis sections, whereas in ILD sections, galectin-3 was expressed in interstitial fibrosis and inflammatory cells. Conclusion: Galectin-3 may be involved in the pathogenesis of inflammatory and fibrotic conditions in IIM and can serve as a potential biomarker of disease activity, especially in patients with IIM-ILD.